Information technology management - Hussain, K. M. (Khateeb M.), 1924- (Computer weekly professional series., 1997)
The purpose of this book is to help you gain an understanding and appreciation of information resource management for your future role as a manager or user of information technology. You will discover that concepts applicable to the management of 'things' and physical property do not apply to the management of information. Many of the basic assumptions in the management of materials and manufactured goods do not apply to information. No wonder a course on 'strategies of information management' - one that teaches how to manage computing resources using contemporary technology in an effective and profitable way - has been added to the curriculum of most schools of business and commerce and to many internal corporate management training programmes. It explains why so many corporate managers and users of information are studying books such as this one.